PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA RISKA. HANDMADE KOTA TANGERANG SELATAN - Sultan Khalik Firdaus; Retno Wulansari (LAP4B, 2025)
This research aims to determine the influence of price and service quality on purchasing decisions at Riska. Handmade South Tangerang either partially or simultaneously. The research method used a quantitative method that was associative in nature. The sampling technique used in this research was 100 respondents. Data analysis techniques used instrument tests, namely validity and reliability tests, classic assumption tests, namely normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, simple linear regression test, multiple linear regression test, correlation coefficient test, determination coefficient test and hypothesis test, namely t test and f test. The results of this research were that price has a significant effect on purchasing decisions. By testing the hypothesis, the t value was obtained tcount > ttable (12.838 > 1.984). Service quality has a significant effect on purchasing decisions. By testing the hypothesis, the t value was obtained tcount > ttable (13.678 > 1,984). Price and service quality simultaneously have a significant effect on purchasing decisions with hypothesis testing obtained fcount > ftable (122.978 > 3.090). Thus, could be concluded that price and service quality have a positive and significant effect on purchasing decisions at Riska. Handmade. The coefficient of determination of influence or contribution of simultaneous influence was 0.717 or 71.7%, the remaining 28.3% was influenced by other factors